2015
DOI: 10.1002/pdi.1925
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ perceptions of injecting insulin and self‐monitoring of blood glucose in the presence of others

Abstract: The aim of this study was to determine if patients with insulin treated diabetes report problems with injecting insulin and self-monitoring of blood glucose (SMBG) in front of others and, if so, explore reasons for the problem.Seventy-six randomly selected patients completed a questionnaire. Statements were presented as 'Are you comfortable with injecting insulin/doing a blood glucose test in front of partner/own children/family/friends/work colleagues or in a public place?', and scored as: almost always/most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“… T1DM ( n = 64) Non-insulin T2DM ( n = 76) Insulin T2DM ( n = 160) Recruited from online panels and by HCPs Online and face-to-face surveys Leiter [ 57 ] 2005 Canada T1DM & Insulin T2DM Patients only To assess impact of mild, moderate and severe hypoglycaemia and fear of future episodes on patients with T1DM or insulin-treated T2DM Adults with insulin treated T2DM ( n = 335) T1DM ( n = 202) insulin T2DM ( n = 133) Diabetes Clinics Self-administered questionnaire Leiter [ 58 ] 2014 Canada Insulin T2DM Patients and HCPs To assess the frequency and impact of dosing irregularities and self-treated hypoglycaemia in T2DM patients treated with insulin analogues in the GAPP2 study. Patients with Insulin treated T2DM ( n = 156) Physicians (n = 202) Of which: PCPs ( n = 160) Specialists ( n = 42) Online panels and HCP registers Online survey Mehmet [ 59 ] 2015 UK T1DM & Insulin T2DM Patients only To determine if patients report problems with injecting insulin/SMBG in front of others and explore reasons why. Insulin T2DM ( n = 27) T1DM ( n = 49) Hospital Clinic Self-completed questionnaire Mitchell [ 60 ] 2013 UK Insulin T2DM & Non-insulin T2DM Patients only To characterize hypoglycaemic events in T2DM and assess the relationship between the experiences and health outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… T1DM ( n = 64) Non-insulin T2DM ( n = 76) Insulin T2DM ( n = 160) Recruited from online panels and by HCPs Online and face-to-face surveys Leiter [ 57 ] 2005 Canada T1DM & Insulin T2DM Patients only To assess impact of mild, moderate and severe hypoglycaemia and fear of future episodes on patients with T1DM or insulin-treated T2DM Adults with insulin treated T2DM ( n = 335) T1DM ( n = 202) insulin T2DM ( n = 133) Diabetes Clinics Self-administered questionnaire Leiter [ 58 ] 2014 Canada Insulin T2DM Patients and HCPs To assess the frequency and impact of dosing irregularities and self-treated hypoglycaemia in T2DM patients treated with insulin analogues in the GAPP2 study. Patients with Insulin treated T2DM ( n = 156) Physicians (n = 202) Of which: PCPs ( n = 160) Specialists ( n = 42) Online panels and HCP registers Online survey Mehmet [ 59 ] 2015 UK T1DM & Insulin T2DM Patients only To determine if patients report problems with injecting insulin/SMBG in front of others and explore reasons why. Insulin T2DM ( n = 27) T1DM ( n = 49) Hospital Clinic Self-completed questionnaire Mitchell [ 60 ] 2013 UK Insulin T2DM & Non-insulin T2DM Patients only To characterize hypoglycaemic events in T2DM and assess the relationship between the experiences and health outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Social factors included stigma, family and friends, economics, work and social activities. Perceived stigma relating to injecting in public was associated with insulin adherence [ 36 , 39 , 41 43 , 59 ]. For some this stigma was reflected in the belief that others perceived injecting insulin as being associated with drug addiction [ 36 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some expressed concern that they wanted to learn more about how to self-manage their disease, but it was hard for them to nd the information (20). A systematic review of 20 studies revealed that patients wanted to know more about diabetes, knowledge and communication with the healthcare provider was a signi cant barrier to receiving and understanding diabetes education (43). The study results are similar to another study conducted in Chennai India on 153 patients which revealed that only 37 (24.1%) patients were aware about the SMBG and have been following self-blood glucose monitoring appropriately (28).…”
Section: Facilitators For Smbgmentioning
confidence: 99%
“…36,52 Social concerns are often related to perceived social stigma, which can result in, for example, a reluctance to inject insulin in public or around family members. 37,65 The fear that using basal insulin will interfere with the patient's daily routine is likely to have a negative effect on several aspects of their social life. 15,25,37,46 In the Japanese population of the DAWN trial, avoiding social stigma was cited as an issue by 55% of patients and only 7% of physicians.…”
Section: Social Concernsmentioning
confidence: 99%